Four-year secukinumab treatment outcomes in European real-world patients with axial spondyloarthritis and psoriatic arthritis - Pons, Marion; Georgiadis, Stylianos; Østergaard, Mikkel; Ahmadzay, Zohra Faizy; Glintborg, Bente; Heberg, Jette; Christensen, Sara Nysom; Rasmussen, Simon; Loft, Anne Gitte; Castrejón, Isabel; Sánchez-Alonso, Fernando; Iannone, Florenzo; et al. (Joint bone spine, 2025)
OBJECTIVES: In axial spondyloarthritis (axSpA) and psoriatic arthritis (PsA) patients initiating secukinumab, we aimed to assess retention rates and proportions of patients achieving remission and low disease activity (LDA), according to disease activity measures and patient-reported outcomes at 24 and 48 months. PATIENTS AND METHODS: Data on patients with axSpA and PsA who initiated secukinumab treatment were pooled from 13 European registries. Analyses were performed overall and stratified according to the number of previous biologic/targeted synthetic Disease-Modifying Antirheumatic Drugs (b/tsDMARDs, 0/1/≥2). Kaplan-Meier plots and Cox regression analyses were performed to assess and compare secukinumab retention rates. Comparisons of remission and LDA rates were performed by logistic regression analyses. RESULTS: The overall 24-/48-month secukinumab retention rates were 61%/51% in 767 axSpA patients, and 64%/49% in 975 PsA patients, respectively. Compared to b/tsDMARD naïve patients, a higher risk of withdrawal from secukinumab was found for those with≥2 prior b/tsDMARDs in axSpA and PsA, and 1 prior b/tsDMARD in axSpA. Generally, remission and LDA rates were numerically higher in b/tsDMARD naïve patients. After adjustment for confounders, statistically significantly higher remission and LDA rates were found for b/tsDMARD naïve patients compared to patients with≥ 2 prior b/tsDMARDs at 24 months in axSpA and PsA. CONCLUSION: This large European real-world study demonstrates that 4-year secukinumab retention rates were approximately 50% in both axSpA and PsA. b/tsDMARD naïve patients had higher retention, remission and LDA rates than patients with prior b/tsDMARD exposure.
Keywords: výsledek terapie; Axial Spondyloarthritis; Male; následné studie; Arthritis, Psoriatic; Europe; Adult; Spondyloarthritis; dospělí; mužské pohlaví; Epidemiology; registrace; Severity of Illness Index; Follow-Up Studies; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; Evropa; Time Factors; Treatment Outcome; axiální spondyloartritida; bDMARD; hodnocení výsledků péče pacientem; lidé; ženské pohlaví; Patient Reported Outcome Measures; Humans; psoriatická artritida; časové faktory; Antirheumatic Agents; antirevmatika; Registries; stupeň závažnosti nemoci; Female; lidé středního věku; indukce remise; Middle Aged; Remission Induction